Metagenome-based diversity and functional analysis of culturable microbes in sugarcane - Haidong Lin; Liang Wu; Lijun Zhang; Quang Kiet Ta; Peng Liu; Jinkang Song; Xiping Yang (Microbiology Spectrum)
ABSTRACT Sugarcane is a key crop for sugar and energy production, and understanding the diversity of its associated microbes is crucial for optimizing its growth and health. However, there is a lack of thorough investigation and use of microbial resources in sugarcane. This study conducted a comprehensive analysis of culturable microbes and their functional features in different tissues and rhizosphere soil of four diverse sugarcane species using metagenomics techniques. The results revealed significant microbial diversity in sugarcane’s tissues and rhizosphere soil, including several important biomarker bacterial taxa identified, which are reported to engage in several processes that support plant growth, such as nitrogen fixation, phosphate solubilization, and the production of plant hormones. The Linear discriminant analysis Effect Size (LEfSe) studies identified unique microbial communities in different parts of the same sugarcane species, particularly Burkholderia, which exhibited significant variations across the sugarcane species. Microbial analysis of carbohydrate-active enzymes (CAZymes) indicated that genes related to sucrose metabolism were mostly present in specific bacterial taxa, including Burkholderia, Pseudomonas, Paraburkholderia, and Chryseobacterium. This study improves understanding of the diversities and functions of endophytes and rhizosphere soil microbes in sugarcane. Moreover, the approaches and findings of this study provide valuable insights for microbiome research and the use of comparable technologies in other agricultural fields.IMPORTANCEThis work utilized metagenomics techniques for conducting a comprehensive examination of culturable microbes and their functional characteristics in various tissues and rhizosphere soil of four distinct sugarcane species. This study enhances comprehension of the diversity and functions of endophytes and rhizosphere soil microbes in sugarcane. Furthermore, the methodologies and discoveries of this work offer new perspectives for microbiome investigation and the use of similar technologies in other agricultural fields.